Relationship between quality of customer care and satisfaction regarding financial services provided by Coopac Prisma, Juanjuí - Cabanillas Cacho, Diana Melissa (2023)
Customer care quality and service satisfaction are important components to improve the relationship and communication with customers, and to generate customer loyalty. There is a growing number of competitors offering similar products and providing customized and prompt customer care, which influences customers in terms of generating loyalty. In this regard, the purpose of this article is to determine the relationship between the quality of customer care offered to members and satisfaction with financial services at a credit cooperative. The approach of the study is quantitative, and the design is non-experimental and transactional, while data collection is prolective because data comes from a primary source. Furthermore, data was collected by means of a survey and the instrument was a questionnaire, with reliability verified by Cronbach's Alpha, which reached 0.921 and 0.902 for the variables customer care quality and service satisfaction, respectively. The sample comprised 205 members of the Juanjuí branch, who were selected by simple random sampling. Finally, it is concluded that there is a relationship between customer care quality and service satisfaction regarding the financial services provided by Coopac MF Prisma at the Juanjuí branch, San Martín, in 2021, with a chi-square value of 194.662 with p = 0.000 < 0.05, and with a Spearman correlation coefficient of 0.724, which is positive and moderate.